The Urgency of Legal Justice in Determining the Timeframe for Filing a Lawsuit with the Administrative Court - Bita Gadsia Spaltani; Sobirin Malian (JURNAL AKTA, 2026)
The deadline for filing a lawsuit to the PTUN is legally based on Article 55 of Law No. 51 of 2009. This study aims to examine the 90-day deadline that has been regulated in the PTUN Law, how its implications for the rights of citizens who are lost due to the lack of procedural flexibility in proceedings at the PTUN. The urgency of this research is to explain more deeply the urgency of legal justice related to the deadline for filing a lawsuit to the PTUN. This is because so far many cases have been NO or declared unacceptable only because of formal reasons such as the expiration of the lawsuit submission that is more than 90 days. So is this legal norm relevant if it is used continuously in resolving TUN disputes. The approach method used in this study is to use a normative juridical approach that examines law as a system and construction of norms by analyzing it from the aspects of legislation, legal principles, doctrines, and court decisions. The results of the discussion, first, the deadline for filing a lawsuit is regulated normatively through Article 55 of the PTUN Law, which stipulates that a lawsuit must be filed within a 90-day time limit from the receipt or announcement of the KTUN. This regulation is especially for parties who are directly addressed by the KTUN object of the dispute. Regarding third parties who are not directly addressed, the judge refers to the jurisprudence of several previous decisions and refers to SEMA No. 2 of 1991 which was updated in SEMA No. 3 of 2015. Second, related to the many N.O decisions due to the expiration of the lawsuit submission before the judge can examine the main case, judicial activism becomes important but also does not mean violating formal rules. Judges play an important role in upholding legal certainty so that it can run in line with the principle of substantive justice without eliminating the rights of citizens.